Challenges of Conducting Clinical Trials during the SARS-CoV-2 Pandemic: The ASCEND Global Program Experience. Issue 4 (28th April 2022) - Johansen, Kirsten L.; Acharya, Anjali; Cizman, Borut; Cobitz, Alexander R.; Correa-Rotter, Ricardo; Dasgupta, Indranil; Kher, Vijay; Lopes, Renato D.; Matsumoto, Leonardo; Meadowcroft, Amy M.; Merege Vieira Neto, Osvaldo; Okabe, Marilu; et al.
Key Points: The coronavirus disease 2019 pandemic has had an unprecedented effect on health and health care and posed challenges to the conduct of clinical trials. Targeted mitigating strategies, on the basis of early and continued data collection from site surveys, limited disruption to the ASCEND trials. Flexibly allowing hemoglobin assessment at local laboratories to inform randomized treatment dosing was key to limiting the discontinuation of treatment.